PELATIHAN PEMANFAATAN MEDIA SOSIAL INSTAGRAM DALAM MEMPUBLIKASIKAN PANTAI TANJUNG PAKIS - Dewi, Nita Komala; Astuti, Hani; Sumartono, Sumartono (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Instagram social media has become one of the platforms for interacting and broadcasting about one's daily activities, but not infrequently Instagram social media can be used as a means of promotion with persuasive content and caption. The method used in this activity is mentoring and peer teaching in the hope that the material delivered by the service team can be well received and the purpose of this activity is to provide additional knowledge and insights to participants regarding the use of social media Instagram in publicizing the tourist attraction of Tanjung Fern Beach. one tourist destination which is located not far from where all participants live and can utilize it wisely and wisely. The participants of the training were 25 youth from the village of Karang Pakis Jaya and the results of this training were 25 Instagram accounts that were used as a media to promote Tanjung Pakis beach.Â Keyword : social media, Tourist destination, promotion